Integrative Ayurveda Management in Functional Recovery of Ardita (Bell’s Palsy): A Case Report - Aishwarya Magdum; G Krishnapriya; Aashish Patel; Vijay Bhaskar (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Bell’s palsy is an acute-onset, unilateral lower motor neuron facial nerve palsy affecting 20-30 per 100,000 population annually. Contemporary management primarily includes corticosteroids and antiviral therapy; however, recovery may be delayed, and some patients experience residual deficits. In Ayurveda, Bell’s palsy closely resembles Ardita, a Vataja Nanatmaja disorder, characterized by facial deviation, impaired eye closure, slurred speech and loss of nasolabial fold. Clinical Findings: A 53-year-old male presented with deviation of mouth, headache, heaviness on left side of face, pricking sensation and watering of both eyes for 15 days. Neurological examination revealed involvement of the facial nerve with loss of the nasolabial fold, incomplete eyelid closure, deviation of angle of mouth and air leakage during cheek inflation, while the remaining cranial nerves and motor functions of limbs were normal. Based on clinical evaluation, the case was diagnosed as Bell’s palsy from the contemporary perspective and Ardita according to Ayurveda. Interventions: The patient was managed with Panchakarma procedures, namely Nasya along with external therapies comprising initial Rukshana with Udvartana, Dashamoola Parisheka and Salvana Upanaha, Sarvanga Abhyanga with Mahamasha Taila followed by Bashpa Sweda, Physiotherapy, and appropriate internal Shamana medications. Outcomes: Progressive clinical improvement was observed during course of treatment, with complete resolution of headache, facial heaviness, eye watering and mouth deviation by the time of discharge. No adverse events were reported during treatment, and no recurrence was observed during 30-day follow-up. House-Brackmann Scale score improved from Grade III to Grade I. Conclusion: This case describes the management of acute-onset Ardita (Bell’s palsy) using integrative Ayurvedic protocol. Favorable clinical recovery was observed during the documented follow-up period. As this is a single case, the findings should interpretate cautiously and well-designed controlled clinical studies are required to establish efficacy and generalizability.